Materialising kinship, constructing relatedness: kin group display and commemoration in First Intermediate Period and Middle Kingdom Egypt (ca 2150–1650 BCE) - Olabarria, L (2014)
The aim of this thesis is to contribute to the understanding of ancient Egyptian kinship in the First Intermediate Period and Middle Kingdom (ca 2150–1650 BCE) by exploring how forms of relatedness were displayed in the monumental record. Kinship and marriage are contextually driven sociocultural phenomena that should be approached from the actors' perspective; such an approach can achieve some insight into emic notions of kinship, because monuments were integral to society and contributed to perpetuating and sustaining its fabric. The introduction (chapter 1) presents the theoretical background on which the thesis is based, namely the notion of kinship as process, where relationships can be constructed and reconstructed throughout one’s life. In addition, it provides a working definition of 'kin group', an analytical category that is taken as the primary unit of social analysis that can encompass several ways of being related. Chapter 2 offers a discussion of kinship terminology in the First Intermediate Period and Middle Kingdom. The focus is less on basic kinship terms than on the little understood terminology for kin groups and how these were presented in the written record. Chapter 3 treats stelae, which constitute the core corpus of material for the thesis. Stelae present a variety of images of kin groups and, moreover, they should be considered within the larger units of which they were part. Many of these stelae are unprovenanced but have been attributed to Abydos. At this site, memorial chapels have been identified archaeologically, and some stelae have been found in association with them. Thus, the site offers a materialisation of constellations of relationships. Possible reconstructions of such chapels – one from Saqqara and two from Abydos – are presented in chapter 4, and the impact they may have had on the social memory of visitors is assessed. Display, presence, and performance were some of the ways in which the social role of those groups was communicated. Chapter 5 is concerned with how change and time may be represented in apparently static objects. On the basis of the model of the developmental cycle of domestic groups first introduced by Meyer Fortes, the dynamism of the social fabric is explored through three case studies of groups at different stages of their developmental cycle. The strategies of survival can be seen pervasively in the monumental record, allowing for a glimpse into time and change in kin groups. The conclusion (chapter 6) offers a holistic approach to the material presented in the thesis, emphasising the ways in which the different theoretical approaches proposed intertwine with the material.